NVTIA™ Standardized Tri-Extract System (Milk Thistle–Artichoke–Dandelion Root) for Bile-Secretion-Oriented Hepatic Support: Botanical Standardization, Mechanistic Rationale, and Evidence Synthesis - Yassine, Jabar; Semenza, Gregg L.; Cortez, Emilio (International Journal of Agriculture and Food Sciences Research, 2026)
Background: Multi-botanical liver-support formulations are increasingly positioned around bile flow, oxidative stress control, and hepatocyte protection, yet the scientific value of such products depends on whether botanical standardization, dose–response behavior, and external evidence converge. Methods: We evaluated the NVTIA tri-extract formulation-series dataset together with a targeted search of PubMed, PMC, and regulatory monographs through March 2026 to identify clinical, mechanistic, and preclinical evidence relevant to milk thistle, artichoke, and dandelion root. Results: Within the formulation series, marker-standardized extracts exceeded predefined quality thresholds (silymarin 83.5%, cynarin 3.2%, total flavonoids 4.8%). Increasing milk thistle from 20 to 50 parts was associated with monotonic improvement in oxidative-stress endpoints, with MDA reductions from 51.27% to 68.17%, SOD increases from 98.62% to 141.53%, and GSH-Px increases from 112.35% to 162.48%. Increasing dandelion root from 15 to 45 parts was associated with 4 h bile-flow increases from 52.78% to 86.11%, ALT reductions from 62.35% to 81.26%, and MDA reductions from 53.47% to 66.78%. In the public literature, a 2024 meta-analysis of nine clinical trials reported significant reductions in ALT and AST with silymarin in MASLD, while a separate 2024 meta-analysis of 26 randomized trials found improvement in liver injury and steatosis outcomes. Two meta-analyses of artichoke supplementation reported significant reductions in ALT and AST, and a placebo-controlled NAFLD trial found improvements in liver enzymes, bilirubin, and sonographic parameters. A placebo-controlled crossover study also documented a marked short-term increase in bile secretion after standardized artichoke extract. By contrast, dandelion-root evidence remained predominantly preclinical. Conclusion: The NVTIA tri-extract framework shows internal dose–response coherence and aligns most strongly with the external evidence base when milk thistle is interpreted as the hepatocyte-protective anchor, artichoke as the bile-oriented functional driver, and dandelion root as an antioxidant and adjunctive biliary-support component. The current literature supports biological plausibility and formulation rationale, while definitive human efficacy for the full tri-extract system still requires prospective clinical validation.